Ultra-highly sensitive HCl-LITES sensor based on a low-frequency quartz tuning fork and a fiber-coupled multi-pass cell - Shunda Qiao; Angelo Sampaolo; Pietro Patimisco; Vincenzo Spagnolo; Yufei Ma (Photoacoustics, 2022)
In this paper, an ultra-highly sensitive light-induced thermoelastic spectroscopy (LITES) based hydrogen chloride (HCl) sensor, exploiting a custom low-frequency quartz tuning fork (QTF) and a fiber-coupled multi-pass cell (MPC) with optical length of 40 m, was demonstrated. A low resonant frequency of 2.89 kHz of QTF is advantageous to produce a long energy accumulation time in LITES. Furthermore, the use of an MPC with the fiber-coupled structure not only avoids the difficulty in optical alignment but also enhances the system robustness. A distributed feedback (DFB) diode laser emitting at 1.74 µm was used as the excitation source. Under the same operating conditions, the using of low-frequency QTF provided a ~2 times signal improvement compared to that achieved using a standard 32 kHz QTF. At an integration time of 200 ms, a minimum detection limit (MDL) of 148 ppb was achieved. The reported sensor also shows an excellent linear response to HCl gas concentration in the investigated range.